Electrophoretic profile of bull sperm membrane proteins as a tool for selection of breeding bull - KARUNAKARAN, M; DEVANATHAN, T G; JAWAHAR, TILAK PON; MANIMARAN, K; CHITRA, ANAND; DHALI, A; SELVARAJU, S (The Indian Journal of Animal Sciences, 2012)
Proteins present in the seminal plasma and sperm influence sperm function and fertilization. The present study was carried out to characterize the electrophoretic profile of bull sperm membrane proteins and to correlate with bull fertility. Semen samples were collected from 20 breeding bulls (10 Jersey and 10 Jersey crossbred) and the sperm membrane proteins were extracted by Triton X. Heparin binding proteins were eluted with heparin column, and the molecular weight of the proteins was assessed by discontinuous sodium dodecyl sulphate polyacrylamide gel elecrophoresis (SDS- PAGE). To assess the field fertility of the bulls, 50 frozen semen straws/bull were used for insemination. Results indicated that only 50 % of the bulls screened had 28– 30 kDa heparin binding proteins in their sperm and these bulls had 12 % higher conception than the bulls lack the protein. So, it can be concluded that the bulls positive for of 28– 30 kDa heparin binding proteins in sperm membrane protein had higher chance of fertility and screening for its presence can be used as a tool in addition to routine criteria for selecting bulls.